2005
DOI: 10.1152/ajplung.00015.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of p47phoxgene deletion on ROS production and oxygen sensing in mouse carotid body chemoreceptor cells

Abstract: . Effect of p47 phox gene deletion on ROS production and oxygen sensing in mouse carotid body chemoreceptor cells. Am J Physiol Lung Cell Mol Physiol 289: L916 -L924, 2005; doi:10.1152/ajplung.00015.2005.-Membrane potential in oxygensensitive type I cells in carotid body is controlled by diverse sets of voltage-dependent and -independent K ϩ channels. Coupling of PO2 to the open-closed state of channels may involve production of reactive oxygen species (ROS) by NADPH oxidase. One hypothesis suggests that ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 48 publications
5
50
0
2
Order By: Relevance
“…In these studies, the neuroprotective properties of apocynin and DPI were associated with inhibition of microglial NADPH oxidase activity, but the role of neuronal NADPH oxidase was not investigated. The neuroprotective effects observed in this study with AEBSF, another NADPH oxidase inhibitor, are also in agreement with studies demonstrating AEBSF prevents NADPH oxidase-induced ROS generation, and cytotoxic and apoptotic cell death in non-neuronal tissues (He et al, 2005;Polytarchou and Papadimitriou, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…In these studies, the neuroprotective properties of apocynin and DPI were associated with inhibition of microglial NADPH oxidase activity, but the role of neuronal NADPH oxidase was not investigated. The neuroprotective effects observed in this study with AEBSF, another NADPH oxidase inhibitor, are also in agreement with studies demonstrating AEBSF prevents NADPH oxidase-induced ROS generation, and cytotoxic and apoptotic cell death in non-neuronal tissues (He et al, 2005;Polytarchou and Papadimitriou, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, there are some observations in our previous experiments (He et al, 2005) and in those of Kevin et al (2003) that do not fit the reliability concept, i.e., that dihydroethidium, upon its reaction with ROS (mostly O 2 •− ), generates fluorescent oxidized products which remain trapped inside the cells and therefore quantification of the fluorescence yields a measurement of the amount of ROS produced. In both of these studies it has been found that short pulses of sodium azide or full ischemia generated fluorescent signals that disappear on the elimination of the sodium azide or on restitution of the flow.…”
Section: General Concepts On Free Radicals and Rosmentioning
confidence: 80%
“…First, based in preliminary evidence (He et al, 2004, also unpublished), we have included CB chemoreceptor cells as a specific place of expression of Nox4 because we have immunocytochemically located it in chemoreceptor cells and found that its transcription rate increases in animals exposed to a 10% atmosphere for 7 days. Second, we ascribe a role to Nox4 in oxygen chemoreception because we have provided evidence that NADPH oxidase-derived (Nox4) derived ROS act as negative second messengers of the hypoxic transduction cascade in chemoreceptor cells and the overall oxygen chemoreception process (He et al, 2005; see article by Dinger et al, 2007). It should be mentioned that in addition to Nox4 we have searched for Nox2 in CB sections and found that it does not co-localize with the chemoreceptor cell marker tyrosine hydroxylase, its expression being restricted to the stroma of the organ.…”
Section: Napdh Oxidasementioning
confidence: 99%
See 2 more Smart Citations